Comparison of Methicillin-resistant Versus Susceptible Staphylococcus aureus Pediatric Osteomyelitis. Issue 5 (May 2018) - Davis, William T.; Gilbert, Shawn R.
Abstract : Background: The incidence of methicillin-resistant Staphylococcus aureus (MRSA) pediatric osteomyelitis has risen and been associated with a more severe clinical course than methicillin-susceptible Staphylococcus aureus (MSSA) infections. National databases have been underutilized to describe these trends. We compared demographics, clinical course, and outcomes for patients with MRSA versus MSSA osteomyelitis. Methods: We queried the 2009 and 2012 Healthcare Cost and Utilization Project Kids Inpatient Database for discharge records with diagnosis codes for osteomyelitis and S. aureus . We explored demographics predicting MRSA and evaluated MRSA versus MSSA as predictors of clinical outcomes including surgery, sepsis, thrombophlebitis, length of stay, and total charges. Results: A total of 4214 discharge records were included. Of those, 2602 (61.7%) had MSSA and 1612 (38.3%) had MRSA infections. Patients at Southern and Midwestern hospitals were more likely to have MRSA than those at Northeastern hospitals. Medicaid patients' odds of MRSA were higher than those with private insurance, and black patients were more likely to have MRSA compared with white patients. MRSA patients were more likely to undergo multiple surgeries compared with MSSA patients and were more likely to have complications including severe sepsis, thrombophlebitis, and pulmonary embolism. Patients with MRSA had longer lengths of stay than those with MSSA and higher total charges after controlling for length of stay. Conclusion: Review of a national database demonstrates MRSA is more prevalent in the South and Midwest regions and among black patients. MRSA patients have more surgeries, complications, and longer lengths of stay. Level of Evidence: Level III. Abstract : Supplemental Digital Content is available in the text.